(untitled) (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2020)
This study aims to determine the effect between Work Discipline and Organizational Culture for Job Satisfaction. The variables used are Work Discipline and Organizational Culture as independent variables and Job Satisfaction variables as the dependent variable. The purpose of this study is to determine and analyze 1) The effect of Work Discipline on employees Job Satisfaction of Pizza Hut East Jakarta Region 2) The effect of Organizational Culture on employees Job Satisfaction of Pizza Hut East Jakarta Region 3) The effect of Work Discipline and Organizational Culture on employees Job Satisfaction of Pizza Hut East Jakarta Region